Solar adsorption cooling system operating by activated–carbon–ethanol bed - Mohammed, Mena Safaa; Farman Alhialy, Nibal Fadel (International Journal of Renewable Energy Development, 2024)
One efficient way to convert small thermally energized into effective cooling is through adsorption cooling technology, which increases energy efficiency and reduces environmental pollution.  This study's primary goal is to hypothetically examine the thermal coefficient of performing the solar adsorptive refrigerator machine operated with an activating carbon/Ethanol operating dual. The impact of different operating situations and design factors on the machine's performance is inspected and evaluated. The present double-bed solar energy adsorptive-cooler unit is modeled by thermodynamic methodology.  Then, it was analyzed to evaluate its effectiveness work under Baghdad climate conditions. For the current study, the two-bed solar adsorption cooling unit with 0.5 kW capacity input heat 11893 that operates at 5 °C for the evaporator and 45 °C for the condenser is presented. The Engineering-Equation-Solver (EES) simulation program was created and used to solve the modeling equations that predict the optimal cycle performance and evaluate the optimum reasonable values of the operation parameters of the proposed system. The pressure range for the refrigeration cycle is 2.408 kPa for the evaporation state and 23.14 kPa for the condensation state. The findings demonstrate that an optimum coefficient of performance (COP) is 0.702 at 95 °C, a 20% performance increase, which generates 39.4 of cooling water. It produced 1 kg of chilled water for 2.463 kg of activated carbon at a temperature of 5°C. The improved solar-powered adsorption systems and refrigeration technologies are appealing substitutes that can satisfy energy demands in addition to meeting needs for cooling, ice production, air conditioning, and refrigeration preservation and safeguarding of the environment with Iraq's climate conditions.